Visualisasi Alat Musik Tradisional Gong Waning Menggunakan Animasi 3D - Nurcahyani Dewi Retnowati; Kristina Nona (Institut Teknologi Dirgantara Adisutjipto, 2017)
Gong Waning is a traditional musical instrument o f Sikka community o f East Nusa Tenggara which is played by beating. In its development, not many young people who can play this instrument. Therefore it is very necessary to design and create an animated model o f the introduction of traditional Gong Waning musical instruments using 3Ds.Max and on sound using unity software. The output o f visualization o f traditional musical instrument Gong Waning in the form o f animation and sound display so hopefully can be more easily in studying and using musical instrument Gong Waning.